Accessing the High‐Q Dark Plasmonic Fano Resonances in Superconductor Metasurfaces. Issue 11 (23rd August 2016) - Srivastava, Yogesh Kumar; Manjappa, Manukumara; Krishnamoorthy, Harish N. S.; Singh, Ranjan
Abstract : Superconducting metamaterials at terahertz frequencies has provided a platform for designing switchable plasmonic metamaterial devices. However, since metals at terahertz frequencies are excellent conductors, the superior role of superconductors in designing low‐loss, high quality factor metamaterials remains unclear. In this work, a low asymmetry Fano resonant split‐ring‐resonator is considered in which a regime of extremely low radiative loss is identified where the high temperature yttrium barium copper oxide superconductor meta‐atom supports a sharp high quality factor Fano resonance while an identical metallic resonator does not show the resonance behavior. The radiative and the nonradiative losses are comparable in low asymmetry Fano resonant meta‐atoms. The observation of high quality factor Fano resonance behavior clearly establishes the utility of superconductors over metals in designing lower loss plasmonic metamaterials at terahertz frequencies that may have multifunctional applications in areas that require strong light–matter interactions. Abstract : Ultrasharp Fano resonances are demonstrated in asymmetric split ring resonator arrays using a high‐temperature superconductor. Ultrahigh‐ Q dark Fano resonances are observed at extremely low structural asymmetry regime which is inaccessible by identical high conductivity metallic structures. Significant line narrowing of superconducting Fano resonance is observed at low and high asymmetry in comparison to metal at terahertz frequencies.